The description of early initiation breastfeeding - Fitria Siswi Utami; Sugiasmini Sugiasmini (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2019)
Early Initiation Breastfeeding (EIB) giving a chance to improve bounding attachment between mother and her infant. Moreover, EIB help to decrease the incidence of postpartum hemorrhage, increase the continuing and period of breastfeeding. The study was conducted to describe the process of EIB in one of district hospital in Yogyakarta Province, Indonesia. A descriptive quantitative method was used to describe factors related to the process of EIB. 150 mothers who giving birth on the period of data collection were recruited as samples. The results show that the number of EIB is 44,7%. The most reason as the obedience of EIB is the limitation number of health care provider (42,86%).